2007
DOI: 10.1111/j.1365-2141.2007.06566.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of de novo acute myeloid leukaemia patients with normal cytogenetics is affected by molecular genetic alterations: a concise review

Abstract: SummaryNormal cytogenetics are detected pretreatment in approximately 45% of patients with de novo acute myeloid leukaemia (AML); thus this constitutes the single largest cytogenetic group of AML. Recently, molecular genetic alterations with prognostic significance have been reported in these patients. They include internal tandem duplication of the FLT3 gene, partial tandem duplication of the MLL gene, mutations of the CEBPA and NPM1 genes and aberrant expression of the BAALC, ERG and MN1 genes. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 84 publications
2
64
0
2
Order By: Relevance
“…Similarly, in normal karyotype AML, patients without FLT3-ITD, TK mutations or MLL-PTD represented almost 50% of AMLs and have a prognosis that is significantly more different than that of patients harboring these mutations. 19 Therefore, we think that our proteomic classification reflects the separation into two subgroups of approximately similar size but different prognostics. Further studies on the correlation between molecular status and proteomics could further improve this issue.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, in normal karyotype AML, patients without FLT3-ITD, TK mutations or MLL-PTD represented almost 50% of AMLs and have a prognosis that is significantly more different than that of patients harboring these mutations. 19 Therefore, we think that our proteomic classification reflects the separation into two subgroups of approximately similar size but different prognostics. Further studies on the correlation between molecular status and proteomics could further improve this issue.…”
Section: Discussionmentioning
confidence: 94%
“…14 It has been demonstrated that NPM1 mutations are associated with specific gene expression signatures. 35,[55][56][57] These transcript signatures are characterized by overexpression of homeobox genes (HOXA, HOXB families and TALE genes). Interestingly, the microRNAs (-10a, -10b, -196a, -196b) that are up-regulated in AML with mutant NPM1, are all located within the genomic cluster of HOX genes.…”
Section: Discussionmentioning
confidence: 99%
“…The ETS transcription factor ERG is overexpressed in subtypes of newly diagnosed T-ALL and AML patients. Overexpression of ERG mRNA expression was further correlated with poor prognosis; however, the downstream effects of deregulated mRNA expression are not yet understood (Baldus et al, 2007). Interestingly, patients with complex cytogenetics attribute aberrant ERG expression to recurring chromosomal abnormalities such as amplification at regions of the ERG loci (Baldus et al, 2004).…”
Section: Discussionmentioning
confidence: 99%